Analysis of A 3-Dimensional Building Frame Considering Outrigger and Hexagrid Technology Using ETABS A Review - Neetu Katre; Abhay Kumar Jha (International Journal of Scientific Research in Civil Engineering, 2021)
The advancement of high strength underlying materials just as the presentation of dominating improvement strategies gave a lift in the advancement of tall constructions. As the tallness of the design builds, they become logically defenseless against wind load and seismic force. The resistance of tall designs to lateral loads is the central determinant in the detailing of new fundamental underlying systems that create by the steady undertakings of primary specialists to continue expanding the structure tallness while keeping the diversion inside commendable places of imprisonment and restricting the proportion of materials. In this proposed work a logical review will be consider on such frameworks like outrigger framework with center shear divider and hex lattice frameworks, to decide their primary productivity in moving the horizontal loads securely to the ground. In this paper we are presenting review of literatures related to analysis of tall structures with lateral load resisting members.